Interaction of complement and leukocytes in severe acute pancreatitis: potential for therapeutic intervention - Hartwig, Werner; Klafs, Martina; Kirschfink, Michael; Hackert, Thilo; Schneider, Lutz; Gebhard, Martha-Maria; Büchler, Markus W.; Werner, Jens (American journal of physiology. Gastrointestinal and liver physiology, 2006)
In acute pancreatitis, local as well as systemic organ complications are mediated by the activation of various inflammatory cascades. The role of complement in this setting is unclear. The aim of the present study was to determine the level of complement activation in experimental pancreatitis, to evaluate the interaction of complement and leukocyte-endothelium activation, and to assess the effects of complement inhibition by soluble complement receptor 1 (sCR1) in this setting. Necrotizing pancreatitis was induced in Wistar rats by the combination of intravenous cerulein and retrograde infusion of glycodeoxycholic acid into the biliopancreatic duct; edematous pancreatitis was induced by intravenous cerulein only. In control animals, a sham operation (midline laparotomy) was performed. Complement activation, leukocyte sequestration, and pancreatic as well as pulmonary injury were assessed in the presence/absence of sCR1. Increased levels of C3a were found in necrotizing but not in edematous pancreatitis. When complement activation in necrotizing pancreatitis was blocked by sCR1, levels of C3a and total hemolytic activity (CH50) were decreased. Leukocyte-endothelial interaction, as assessed by intravital microscopy, and pancreatic as well as pulmonary organ injury (wet-to-dry weight ratio, MPO activity, and histology) were ameliorated by sCR1. As a result of the present study, necrotizing but not edematous pancreatitis is characterized by significant and early complement activation. Based on the interaction of complement and leukocytes, complement inhibition by sCR1 may be a valuable option in the treatment of leukocyte-associated organ injury in severe pancreatitis.
Gesehen am 15.02.2021